ISU KEDUKAAN DALAM METROPOP CRITICAL ELEVEN KARYA IKA NATASSA - Tania Intan; Sri Rijati Wardiani (Balai Bahasa Kalimantan Barat, 2021)
Grief is a condition of human emotion due to loss of something very valuable, which is caused for example by separation or death. This research was conducted to uncover the way in which grief is narrated in Ika Natassa's novel “Critical Eleven”. In addition, this article also studies the stages carried out by the protagonists to eliminate their grief due to the death of their son. The methodological approach used for this study is literary psychology, with a theoretical framework about The Five Stages of Grief from Kübler-Ross. The results showed that: textually, the grief narrative was revealed through actions, attitudes, thoughts, and utterances of characters. The protagonists, Anya and Ale also go through all stages of grief, namely: denying, angry, negotiating, depressed, and finally accepting that reality.